miR-1468-3p Promotes Aging-Related Cardiac Fibrosis - Ruizhu Lin; Lea Rahtu-Korpela; Johanna Magga; Johanna Ulvila; Julia Swan; Anna Kemppi; Lasse Pakanen; Katja Porvari; Heikki Huikuri; Juhani Junttila; Risto Kerkelä (Elsevier, 2020)
Non-coding microRNAs (miRNAs) are powerful regulators of gene expression and critically involved in cardiovascular pathophysiology. The aim of the current study was to identify miRNAs regulating cardiac fibrosis. Cardiac samples of age-matched control subjects and sudden cardiac death (SCD) victims with primary myocardial fibrosis (PMF) were subjected to miRNA profiling. Old SCD victims with PMF and healthy aged human hearts showed increased expression of miR-1468-3p. In vitro studies in human cardiac fibroblasts showed that augmenting miR-1468-3p levels induces collagen deposition and cell metabolic activity and enhances collagen 1, connective tissue growth factor, and periostin expression. In addition, miR-1468-3p promotes cellular senescence with increased senescence-associated β-galactosidase activity and increased expression of p53 and p16. AntimiR-1468-3p antagonized transforming growth factor β1 (TGF-β1)-induced collagen deposition and metabolic activity. Mechanistically, mimic-1468-3p enhanced p38 phosphorylation, while antimiR-1468-3p decreased TGF-β1-induced p38 activation and abolished p38-induced collagen deposition. RNA sequencing analysis, a computational prediction model, and qPCR analysis identified dual-specificity phosphatases (DUSPs) as miR-1468-3p target genes, and regulation of DUSP1 by miR-1468-3p was confirmed with a dual-luciferase reporter assay. In conclusion, miR-1468-3p promotes cardiac fibrosis by enhancing TGF-β1-p38 signaling. Targeting miR-1468-3p in the older population may be of therapeutic interest to reduce cardiac fibrosis.